PENGARUH NPL, LDR, ROA, ROE, NIM, BOPO, DAN CAR TERHADAP HARGA SAHAM PADA SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2008 ???? 2012 - Sigit Dwi Wismaryanto (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2013)
This research aimed to examine the effect of NPL (Non Performing Loan), LDR (Loan to Deposit Ratio), ROA (Return On Assets), ROE (Return On Equity), NIM (Net Interest Margin), BOPO (Operating Expenses to Operating Income), and CAR (Capital Adequacy Ratio) on stock prices in the Banking Sub-Sector were listed on the Indonesia Stock Exchange in the period 2008 to 2012. Number of samples taken through purposive sampling method is as much as 24 of the total population of 32 commercial banks. Analysis technique using multiple linear regression analysis, whereas hypothesis testing using simultaneous significance test (test statistic F) and partial test of significance (t statistic test). Based on the classical assumption, there is multicollinearity between ROA and ROE variables. Therefore, the researcher chose to drop the ROE variable. The results showed that simultaneously, NPL, LDR, NIM and ROA significantly. LDR ratio had significant negative effect. NIM ratio had significant positive and ROA ratio had significant negative effect on stock prices in the banking sub-sector were listed on the Indonesia Stock Exchange in the year 2008 to 2012. Keywords : NPL, LDR, ROA, ROE, NIM, BOPO, CAR, and Stock Price